Development of a STEM Based E-Module on Motorcycle Electrical Systems to Enhance Creative Thinking Skills in Vocational High School Students - Adi Abdullah; Eges Triwahyuni (JTP - Jurnal Teknologi Pendidikan, 2025)
Facts in the field show the low creative thinking skills of students. Students' difficulties in understanding the material lead to low creative thinking skills. The background of this research in the era of the Industrial Revolution 4.0, students are expected to have creative and solution-oriented thinking skills, so they are able to solve various everyday problems intelligently and productively. The purpose of this research is to develop an electronic module based on Science, Technology, Engineering, and Mathematics (STEM) to improve students' creative thinking skills in motorcycle electrical systems in State Vocational High Schools. The research method used is development research with the ADDIE model. The research subjects were grade XI students in State Vocational High Schools. Data analysis techniques in this study used qualitative and quantitative methods. The results of the creative thinking skills improvement test showed an N-Gain score of 0.45, which is included in the moderate category. Media expert validation results 86.25%, material expert validation 87.50%. The conclusion of this study is that the STEM-based motorcycle electric E-module is feasible to use and can improve creative thinking skills in State Vocational High Schools. This research provides implications that the development of an electronic module based on Science, Technology, Engineering, and Mathematics (STEM) in motorcycle electrical systems can be a reference for teachers in improving creative thinking skills in terms of content, strategies, methods, and teaching approaches.